KESALAHAN PENGGUNAAN KALIMAT BAHASA INDONESIA DALAM SURAT-MENYURAT PADA INSTANSI PEMERINTAH KABUPATEN JAYAPURA - Asmabuasappe dan Antonius Maturbongs NFN (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
The goal of this research is to express about incorrect form for using sentences of formal documents in Pemkab Jayapura and to correct it based on Indonesian effective sentences. Its data resource is the official documents in Pemkab Jayapura, especially in Law and Research Department. The data was collected by documentation study. The research uses descriptive method. The result of this research shows all incorrect form on sentences using of Indonesian. They are incorrect form for using alphabet, phrase, incomplete of sentences unsure, sentences without dot sign, incorrect in their dictions, incorrect in conjunctions.